Calf rearing practices followed by dairy farmers in Valsad district of Gujarat (Indian Journal of Animal Production and Management, 2024)
A field survey was conducted to ascertain the calf rearing practices followed by dairy animals owners in Valsad district of Gujarat. A total of 240 respondents were selected from two randomly selected talukas and interviewed with the help of structured interview schedule. The present study revealed that 97.9% of the respondents attended calving and cleaned the calves soon after parturition. Only 14.20% of respondents followed practice ligation, cutting and disinfection of the naval cord. Majority (67.9%) of the respondents fed colostrum to new born calf within an hour of birth.About 34.2% of the respondents did not followed weaning practice and 35.4% of the respondents allowed calves to suckle their dams till lactation ceased. Only 22.9% of the respondents provided green fodders from two months of age and 27.9% of the respondents provided calf starter to the calves. Majority (72.5%) of respondents practiced castration of male calves and 34.2% of the respondents gave anthelmintic to the calves regularly. Only 16.7% of the respondents provided jacketing as well as bedding in order to protect their calves from cold during winter season. Calf rearing management practices are not being adopted by farmers to certain extent and needs to be improved by organizing training programmes and result demonstration on and off campus extension activities of SAUs, KVK’s and government agencies working in the study area.
Keywords: Calf; Farmers; Practices; Rearing